Sexualidade e Transtorno do Espectro Autista: relatos de familiares - Vieira, Ana Carla [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Sexual education is an ongoing process through which is learned about sexuality aspects; a wide and complex dimension that develops over the people‟s lives in their interactions with social, cultural, economic, historical and biological elements. People with disabilities such as Autism Spectrum Disorder or Asperger Syndrome (TEA/SA) are commonly childlike and the expression of their sexuality is fraught with myths. Also, they do not generally receive sexual education, resulting in lack of knowledge about the subject, limited emotional and sexual experiences and situations of vulnerability. But how does the family take the sexual education of their children with TEA/SA? What do they think about their sexuality? To answer these questions, this qualitative-descriptive research, aimed to investigate the opinions and actions of seven motherson the sexuality of their children with TEA/SA aged between 10 and 22 years. The data were collected through interviews guided from a script, recorded and fully transcribed for further analysis from the organization of thematic categories. The results indicated that there is almost no sexual education by mothers: some of them make use of metaphorical explanation, other ones turn to psychologists or does not talk about it. They said they did not have access to materials that could assist them on this sexual education, and that health and education professionals of their surroundings does not talk or collaborate in this direction. The infantilization of children was an important aspect unveiled in the reports. Also they believed that the sexual desires of people with TEA/SA would be similar to the neurotipical people, but that deficits in social skills related to the disorder greatly harm their on the social, emotional and sexual relationships. Most of them saw their sons masturbating, showing deficits in discrimination between public and private behaviors, and reported dependence on their part to daily self-care activities. A mother mentioned that her son was involved in risky situations because he does not understand social rules. The finding data rectifies those found in the literature especially regarding the lack of intervention on the matter and the difficulties experienced by families to treat it. Furthermore, the data converges with studies that indicate characteristics associated with TEA/SA as obstacles to the sexual development such as deficits on social and communication skills. It is concluded that the guidance by professionals directed to the families of people with TEA/SA can contribute to the viability of an emancipatory sexual education as well as social skills training for young people can enhance their development. It must be recognized the right of people with TEA/SA to express their sexuality in an inclusive society and, therefore, it should guaranteed the access to sexual education throughout their human development.

A educação sexual é um processo contínuo por meio do qual se aprende sobre aspectos da sexualidade; uma dimensão ampla e complexa que se desenvolve ao longo da vida das pessoas em suas interações com elementos sociais, culturais, econômicos, históricos e biológicos. Pessoas com deficiências como o Transtorno do Espectro Autista ou Síndrome de Asperger (TEA/SA) são comumente infantilizadas e a expressão de sua sexualidade é permeada de mitos. Além disso, geralmente não recebem educação sexual, resultando em falta de conhecimento sobre o assunto, vivências afetivas e sexuais limitadas e situações de vulnerabilidade. Mas como os familiares assumem a educação sexual de seus filhos com TEA/SA? O que pensam sobre a sexualidade deles? Para responder essas questões, a presente pesquisa, do tipo qualitativa-descritiva, teve por objetivo investigar as opiniões e ações de sete mães sobre a sexualidade de seus filhos com TEA/SA com idades entre 10 e 22 anos. A coleta de dados ocorreu por meio entrevistas realizadas a partir de um roteiro, gravadas e transcritas na íntegra para posterior análise a partir da organização de categorias temáticas. Os resultados indicaram que quase não há educação sexual por parte das mães: algumas se utilizam de explicações metafóricas, outras recorrem a psicólogos ou não falam sobre o assunto. Afirmaram não ter acesso a materiais que pudessem auxiliá-las nesta educação sexual, e que os profissionais da saúde e da educação de seu entorno não conversaram ou colaboraram neste sentido. A infantilização dos filhos foi um aspecto importante desvelado nos relatos. Também acreditavam que os desejos sexuais de pessoas com TEA/SA seriam parecidos com os de pessoas neurotípicas, mas que os déficits em habilidades sociais relacionados ao transtorno prejudicavam imensamente seus relacionamentos sociais, afetivos e sexuais. A maioria delas viu o filho se masturbando, evidenciando déficits na discriminação entre comportamentos públicos e privados, e relataram dependência por parte deles para atividades de autocuidados diários. Uma mãe citou que o filho se envolveu em situações de risco por não compreender as regras sociais. Os dados coletados retificam os encontrados na literatura especialmente com relação à falta de intervenções sobre o assunto e às dificuldades sentidas pelas famílias para tratá-lo. Além disso, os dados convergem com estudos que indicam as características associadas ao TEA/SA como obstáculos para o desenvolvimento sexual, como déficits em habilidades sociais e comunicação. Conclui-se que a orientação por parte de profissionais voltada às famílias de pessoas com TEA/SA pode contribuir para a viabilização de uma educação sexual emancipatória, assim como o treino de habilidades sociais para os jovens pode potencializar seu desenvolvimento. É preciso reconhecer o direito das pessoas com TEA/SA de expressarem sua sexualidade na sociedade inclusiva e, portanto, deve-se garantir o acesso à educação sexual ao longo de todo seu desenvolvimento humano.
Sexuality and Autism Spectrum Disorder: family reports
Keywords: Autism Spectrum Disorders; Asperger's Syndrome; Sexual Education; Sexuality; Transtorno do Espectro Autista; Síndrome de Asperger; Educação Sexual; Sexualidade